2006
DOI: 10.1029/2006pa001278
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the vertical profile of the Indonesian Throughflow during Termination II: Evidence from the Timor Sea

Abstract: [1] We use a multiproxy approach to monitor changes in the vertical profile of the Indonesian Throughflow as well as monsoonal wind and precipitation patterns in the Timor Sea on glacial-interglacial, precessional, and suborbital timescales. We focus on an interval of extreme climate change and sea level variation: marine isotope (MIS) 6 to MIS 5e. Paleoproductivity fluctuations in the Timor Sea follow a precessional beat related to the intensity of the Australian (NW) monsoon. Paired Mg/Ca and d18 O measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 64 publications
6
70
3
7
Order By: Relevance
“…Xu et al, 2006Xu et al, , 2008Holbourn et al, 2011;Ding et al, 2013]. These studies revealed cooling and freshening of the upper thermocline…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Xu et al, 2006Xu et al, , 2008Holbourn et al, 2011;Ding et al, 2013]. These studies revealed cooling and freshening of the upper thermocline…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Recent studies have suggested that tropical sea surface temperatures (SSTs) increased by 4°C [3][4][5] during the penultimate deglaciation (Termination II), and planktonic foraminifera δ 18 O, which indicates ice volume changes, lagged the Mg/Ca-SST changes by 2000-3000 a [3][4][5][6]. Such great changes in SST have had a *Corresponding authors (email: cct1234@163.com; tianjun@tongji.edu.cn) significant role in regulating global climate change [6,7].…”
mentioning
confidence: 95%
“…Numerous lines of evidence, including data from plankton tows [Fairbanks et aL, 1982], sediment traps Mohtadi et aL, 2009], and coretops Sadekov et al, 2009;Xu et aL, 2006;Zuraida et aL., 2009], suggest that within the modern tropics, P. obliquiloculata has an upper thermocline depth habitat. Our data are consistent with these studies.…”
Section: Geochemistry Of P Obliquiloculata As a Thermocline Indicatormentioning
confidence: 99%